2023
DOI: 10.1002/jsfa.12559
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization mechanism of self‐assembled walnut protein nanoparticles and curcumin encapsulation

Abstract: BACKGROUND: Native walnut protein is an alkali-soluble protein that seriously limits the application of walnut protein. The pHshifting method could improve the solubility of walnut proteins and enable the encapsulation of active ingredients. The present study aimed to prepare water-soluble nanoparticles of curcumin using walnut protein and evaluate the process of walnut protein self-assembly, interaction between walnut protein and curcumin, encapsulation properties, and stability of nanoparticles. RESULTS:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The fluorescence quenching of Cur against walnut protein showed a similar result. 31 According to Fig. 2(D), the n value of 7S-Cur complexes was about 1, which suggested that there was a binding site for 7S to bind with Cur.…”
Section: Intrinsic Fluorescence Spectroscopic Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…The fluorescence quenching of Cur against walnut protein showed a similar result. 31 According to Fig. 2(D), the n value of 7S-Cur complexes was about 1, which suggested that there was a binding site for 7S to bind with Cur.…”
Section: Intrinsic Fluorescence Spectroscopic Analysismentioning
confidence: 86%
“…When curcumin was present, the hydrophobic core of walnut protein took Cur as a core and began to self-assemble around it, eventually forming smaller nanocomplexes. 31 Interestingly, the values of ζ-potential had no significant differences between 7S-pH 12-pH 7 and 7S-Cur, suggesting that 7S nanoparticles could be used as stable delivery carriers for Cur. In addition, the PDI value of 7S-Cur was 0.15, lower than 0.30, indicating that the 7S-Cur composite particles had a good uniformity.…”
Section: Measurements Of ζ-Potential Particle Size and Pdimentioning
confidence: 89%
See 1 more Smart Citation